The Causal Effects of Elite Position‐Taking on Voter Attitudes: Field Experiments with Elite Communication. Issue 1 (15th December 2015) - Broockman, David E.; Butler, Daniel M.
Abstract : Influential theories depict politicians as, alternatively, strongly constrained by public opinion, able to shape public opinion with persuasive appeals, or relatively unconstrained by public opinion and able to shape it merely by announcing their positions. To test these theories, we conducted unique field experiments in cooperation with sitting politicians in which U.S. state legislators sent constituents official communications with randomly assigned content. The legislators sometimes stated their issue positions in these letters, sometimes supported by extensive arguments but sometimes minimally justified; in many cases, these issue positions were at odds with voters'. An ostensibly unrelated survey found that voters often adopted the positions legislators took, even when legislators offered little justification. Moreover, voters did not evaluate their legislators more negatively when representatives took positions these voters had previously opposed, again regardless of whether legislators provided justifications. The findings are consistent with theories suggesting voters often defer to politicians' policy judgments.